2020
DOI: 10.1177/1971400920964715
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverter device placement for cerebral aneurysm is not effective for the patient with parent artery occlusion for contralateral aneurysm

Abstract: Purpose There have been many reports on the risks of enlargement and rupture of residual aneurysms and de novo aneurysm formation in the contralateral internal carotid artery after parent artery occlusion (PAO). In the present study, we investigated the efficacy of flow diverter device placement (FDDP) for the treatment of contralateral internal carotid artery aneurysms after PAO. Methods After 11 patients, who had bilateral large or giant internal carotid aneurysms, were treated for either side with PAO or FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that the occlusion rate is reduced when PAO was performed for the contralateral ICA. 31) After 3 years of long-term follow-up, complete occlusion was achieved. Of the other 4 patients, 1 patient developed in-stent embolus following discontinuation of antiplatelet medication, 1 had complete occlusion with subsequent recurrence, 1 had enlargement after FD implantation, and 1 had gradual occlusion of the FD.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the occlusion rate is reduced when PAO was performed for the contralateral ICA. 31) After 3 years of long-term follow-up, complete occlusion was achieved. Of the other 4 patients, 1 patient developed in-stent embolus following discontinuation of antiplatelet medication, 1 had complete occlusion with subsequent recurrence, 1 had enlargement after FD implantation, and 1 had gradual occlusion of the FD.…”
Section: Discussionmentioning
confidence: 93%